2009
DOI: 10.2460/ajvr.70.9.1102
|View full text |Cite
|
Sign up to set email alerts
|

Use of a polymerase chain reaction assay to study response to oxytetracycline treatment in experimental Candidatus Mycoplasma haemolamae infection in alpacas

Abstract: The PCR assay was more sensitive than blood smear examination for detection of infection. Clinical signs, anemia, and fever were not necessarily associated with infection. Oxytetracyline administration did not consistently clear CMhl infection. Although treated with oxytetracycline, infected alpacas remained chronic carriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
49
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 19 publications
3
49
2
1
Order By: Relevance
“…The assay was used in experimental infections and showed that many camelids are subclinical chronic carriers. Some of the experimentally infected camelids were transiently anemic, while others were not, and they did not develop fever, depression, or hypoglycemia ( 9 The PCR assay had been used diagnostically in more than 6,000 blood samples from all over the United States as well as Australia, Canada, and the United Kingdom. There have been no reports documenting whether infection was present in llamas or alpacas in South America.…”
mentioning
confidence: 99%
“…The assay was used in experimental infections and showed that many camelids are subclinical chronic carriers. Some of the experimentally infected camelids were transiently anemic, while others were not, and they did not develop fever, depression, or hypoglycemia ( 9 The PCR assay had been used diagnostically in more than 6,000 blood samples from all over the United States as well as Australia, Canada, and the United Kingdom. There have been no reports documenting whether infection was present in llamas or alpacas in South America.…”
mentioning
confidence: 99%
“…Although the majority of infected camelids have the asymptomatic chronic form of the infection (3, 6), crias and animals experiencing stress, such as parturition and gestation, may develop severe, life-threatening anemia (acute disease) (4-6). Moreover, "Candidatus Mycoplasma haemolamae" is known to persist in the host despite antibiotic treatment and/or an immune response (10). Mechanisms by which "Candidatus Mycoplasma haemolamae" evades the immune system and causes chronic disease, as well as those that trigger development of acute disease, are poorly understood.…”
mentioning
confidence: 99%
“…These findings are similar to those of a recent study in alpacas, in which treatment with oxytetracycline was not associated with faster clearance of ''Candidatus Mycoplasma haemolamae'' infection. 24 However, in cats, studies 6,7,[20][21][22] using qPCR have demonstrated the effectiveness of both doxycycline and fluoroquinolones in reducing copy numbers of feline hemoplasmas and improving clinical signs, but again, clearance of infection is not always achieved. Given the long duration of treatment with no marked change in M. haemocanis copy numbers, it is likely that the resolution of clinical disease in the present case was due to the development of an effective immune response by the dog.…”
mentioning
confidence: 99%